Granulocyte colony stimulating factor (G-CSF)-induced aortitis in a patient undergoing adjuvant chemotherapy for breast cancer. Issue 1 (17th January 2022) - Asif, Rehan; Edwards, Gwenllian; Borley, Annabel; Jones, Sharon
Abstract : Granulocyte colony stimulating factor (G-CSF) is used to prevent febrile neutropenia post chemotherapy. Usually well tolerated with minimal side effects but aortitis is an extremely rare side effect previously reported. A 64-year-old woman treated with adjuvant chemotherapy including G-CSF for left breast cancer was admitted with fevers, neutropenia and markedly raised inflammatory markers after 7 days of her first cycle. Initially diagnosed with neutropenic sepsis, she did not respond to broad spectrum antibiotics with subsequent CT imaging revealing marked periaortic inflammatory changes consistent with aortitis and periaortitis. Extensive investigations for other causes of large vessel vasculitis were negative and G-CSF was the only causative factor. She rapidly responded to steroids with almost complete resolution of inflammatory changes on repeat imaging within 4 weeks and no recurrence on tapering of steroids. This diagnosis must be considered in patients presenting with fever and raised inflammatory markers post G-CSF treatment.